Unannounced in situ simulations: integrating training and clinical practice. Issue 6 (4th December 2012) - Walker, Susanna T; Sevdalis, Nick; McKay, Anthony; Lambden, Simon; Gautama, Sanjay; Aggarwal, Rajesh; Vincent, Charles
Abstract : Simulation-based training for healthcare providers is well established as a viable, efficacious training tool, particularly for the training of non-technical team-working skills. These skills are known to be critical to effective teamwork, and important in the prevention of error and adverse events in hospitals. However, simulation suites are costly to develop and releasing staff to attend training is often difficult. These factors may restrict access to simulation training. We discuss our experiences of 'in situ' simulation for unannounced cardiac arrest training when the training is taken to the clinical environment. This has the benefit of decreasing required resources, increasing realism and affordability, and widening multidisciplinary team participation, thus enabling assessment and training of non-technical team-working skills in real clinical teams. While there are practical considerations of delivering training in the clinical environment, we feel there are many potential benefits compared with other forms of simulation training. We are able to tailor the training to the needs of the location, enabling staff to see a scenario that is relevant to their practice. This is particularly useful for staff who have less exposure to cardiac arrest events, such as radiology staff. We also describe the important benefit of risk assessment for a clinical environment. During our simulations we have identified a number of issues that, had they occurred during a real resuscitation attempt, may have led to patient harm or patient death. For these reasons we feel in situ simulation should be considered by every hospital as part of a patient safety initiative.